Differences Learning Methods Tutorial with recitation of the Knowledge, Attitudes and Skills Students in Doing Health Promotion - Munjiati Munjiati; Herry Prasetyo; Ulfah Agus Sukrillah (Pusat Penelitian dan Pengabdian kepada Masyarakat, Poltekkes Kemenkes Semarang, 2014)
This research aims to determine the differences in methods of tutorials learning with recitation of the knowledge, attitude and skills of students in promoting health. The populations in this research are 333 nursing students at Purwokerto Nursing Department. Then, we use a cluster sampling method where 80 nursing students at second grade are divided into two groups, an intervention group, consists of 40 students and a control group, consists of 40 students. Then, the data collection is done by using questionnaire and observation sheets. The data obtained were analyzed using the paired t test to analyze differences in each pre and post experiment group. Then, in order to determine the difference between the two methods we use independent sample t test. The research shows that there is increasing average value before and after the use of tutorial method and recitation method. The test results of Independent Sample T test is 0.005. With significance 0,000, it can be concluded that the use of tutorial method is more effective to improve knowledge, attitudes and skills of students in health promotion compared with recitation method.